Interrelationships between costing, packaging, branding and business support of Malaysian SME product value - Faizal, Diana Rose (2017)
The purpose of this study is to examine the interrelationship of costing towards the packaging, branding and business support on SME's product value in supplying to consumers and distribution channel in Malaysia. Knowingly, SMEs is one of the major sources in contributing to the economic growth in Malaysia. This study intends to scrutinize the competently rapid growth of food industry and SMEs in Malaysia. Furthermore, this study extends a cost faced by SMEs manufacturing the F&B products as to emerge a food market practically. A ways to secure in the food market, the product must be valuable. Hence, this study justifies that a valuable product always side to side with high product costs, and other factors should be considered such as packaging and branding. Moreover, this study explains the importance of product value following demand of consumer in Malaysia. This study used the quantitative method by distributing questionnaires to SMEs that comes from F&B background. There were 400 questionnaires collected from the SMEs, specifically respondent from the owner or managers of SMEs. This study uses a non-probability sampling where it a based on the availability and easy access with SMEs. The respondent counterparts all states in Malaysia. Furthermore, a theory such as Transaction Cost and Resource Based View was applied in supporting the proposed of nine relationships and hypotheses. Moreover, this study was carried out using the Partial Least Square Structural Equation Modeling (PLS-SEM). It has passed through two stages in PLS-SEM analysis by developing the measurement model and assessing the structural model. The results of this study showed that eight out of nine hypotheses were supported. A cost in needs is found to be significant with mass product value. The result shows stronger interaction of mediation on the implementation of packaging and branding towards the product value. In brief, business support that symbolizes as moderator has only significant towards the packaging. Nonetheless, it has no moderation effect on the branding. Therefore, SMEs need to put aside a sum of money which is significant to enhance their products' packaging and branding. In addition, SMEs genuinely need help from the business support that comes not only in the form of the financial support but also non-financial support in order to cater the cost as well as improvising the product packaging. Hence, it helps the SMEs in manufacturing the products according to demand of consumer and distribution channel. Altogether, increase the income of SMEs and contributes to the national economic growth.